Streptococcus suis subtilisin-like serine proteases SspA-1 and SspA-2 interplay with complement C3a and C5a to facilitate bacterial immune evasion and infection - Simin Deng; Junhui Liao; Haojie Li; Jiali Xu; Jingyan Fan; Jing Xia; Jing Wang; Lei Lei; Mianmian Chen; Yue Han; Ruidong Zhai; Chang Zhou; et al. (Virulence, 2024)
ABSTRACTStreptococcus suis (S. suis), a significant zoonotic bacterial pathogen impacting swine and human, is associated with severe systemic diseases such as streptococcal toxic shock-like syndrome, meningitis, septicaemia, and abrupt fatality. The multifaceted roles of complement components C5a and C3a extend to orchestrating inflammatory cells recruitment, oxidative burst induction, and cytokines release. Despite the pivotal role of subtilisin-like serine proteases in S. suis pathogenicity, their involvement in immune evasion remains underexplored. In the present study, we identify two cell wall-anchored subtilisin-like serine proteases in S. suis, SspA-1 and SspA-2, as binding partners for C3a and C5a. Through Co-Immunoprecipitation, Enzyme-Linked Immunosorbent and Far-Western Blotting Assays, we validate their interactions with the aforementioned components. However, SspA-1 and SspA-2 have no cleavage activity against complement C3a and C5a performed by Cleavage assay. Chemotaxis assays reveal that recombinant SspA-1 and SspA-2 effectively attenuate monocyte chemotaxis towards C3a and C5a. Notably, the ΔsspA-1, ΔsspA-1, and ΔsspA-1/2 mutant strains exhibit compromised survival in blood, and resistance of opsonophagocytosis, alongside impaired survival in blood and in vivo colonization compared to the parental strain SC-19. Critical insights from the murine and Galleria mellonella larva infection models further underscore the significance of sspA-1 in altering mortality rates. Collectively, our findings indicate that SspA-1 and SspA-2 are novel binding proteins for C3a and C5a, thereby shedding light on their pivotal roles in S. suis immune evasion and the pathogenesis.